Pengaruh kompres hangat terhadap intensitas nyeri persalinan kala I fase aktif - Suyani Suyani (Universitas Muhammadiyah Semarang, 2020)
Pain is an integral part of labor and childbirth which is normal due to physiological and psychological factors. Labor pain can affect uterine contractions through secretion of catecholamine and cortisol levels which increase sympathetic nervous system activity, changes in blood pressure, heart rate, breathing, and consequently affect labor duration. This study aims to determine the effect of warm compresses on the intensity of labor in the first phase of active labor. The design of this study was quasi-experimental with one group pre-test and post-test design. The population in this study were all labor women at BPM Tri Rahayu Setyaningsih Sleman, with incidental sampling techniques and 18 samples were obtained. A compress was carried out in the lower abdomen using hot bladders. Data analysis using Paired T test. Based on the research results obtained, the mean pain score before treatment was 8.66 and the mean pain score after treatment was 5.83. The results of statistical analysis of different pain intensity tests before and after treatment showed a significant difference (p = 0,000; 95% CI -3,352 - (- 2,314). This shows that warm compresses can reduce the intensity of pain in labor during the active phase. warmth can be used as one way to reduce the intensity of labor pain